Students’ Anxiety Towards Learning English at SMA Negeri 9 Weet Maluku Barat Daya - Luklay, Erni Irawati; Rijoly, Helena M; Meyer, Fredi (Koli Journal : English Language Education, 2022)
Learning a new language always comes with a certain level of anxiety. Students reported experiencing anxiety during the learning process. This research looks at students'students' anxiety towards learning English, specifically at SMA Negeri 9 Weet Maluku Barat Daya. This place was chosen because it was far from the province's capital. It will be interesting to see the level of anxiety that these students experience. This qualitative research uses the survey method. The study participants were twenty-two (22) students of Class X of SMA Negeri 9 Weet, MBD. The research aimed to answer two research questions: 1) What level of anxiety do students experience in learning English, and 2) What types of anxiety do students often feel during the process of learning English? The instrument used to collect the data was a questionnaire. The 30-item questionnaire was adopted from Horwits' FLCAS (Foreign Language Classroom Anxiety Scale). Data shows that: 1) The level of student's anxiety towards learning English in first grade (Class X) of SMA Negeri 9 Weet, MBD was indicated as Mildly Anxious. 2) The research's findings indicate that the most dominant student' type of anxiety was communicative apprehension